Pelatihan Perencanaan Bisnis Untuk Siswa SMK Logistik Sumedang - Muhammad Iqbal; Dini Yulianti; Ilham Eka Santang; Agi Agus Setiawan Sofyan; Yayan Mulyana (JAMARI: Jurnal Pengabdian Masyarakat Mandiri, 2024)
The Industrial Engineering Program at Universitas Insan Cendikia Mandiri conducted a community service activity by organizing a business planning training for students of the SMK Logistics in Sumedang. This community service activity aims to provide these vocational high school students with insights into entrepreneurship through the introduction of business planning. Developing entrepreneurial interest among vocational high school students is considered strategic for preparing a productive and character-driven future generation capable of working in the industry, continuing their studies, or becoming creative entrepreneurs. By fostering a business mindset, students will have the option to plan and run their own businesses after graduation